A 45-year-old man with spontaneous hyphema of the right eye - Wang, Jay C. (Digital Journal of Ophthalmology, 2017)
A 45-year-old white man with a history of iritis of the right eye presented to the Massachusetts Eye and Ear Emergency Department for a new, spontaneous hyphema of the right eye. The patient reported that he had previously experienced approximately 4 episodes of iritis of the right eye each year for the last 4 years; each time these episodes resolved with topical steroid therapy. He did not recall any blood work having been performed or any cause of his recurrent iritis having been identified. The current episode started 1 week prior to presentation with pain, redness, and right eye photosensitivity. He was examined by his ophthalmologist 3 days later and was started on topical prednisolone acetate 1% every 2 hours. His symptoms did not improve with this treatment, and 1 day prior to presentation he was noted by his ophthalmologist to have a new hyphema of the right eye and was referred to our institution. The patient did endorse a history of intermittent joint pains, worse in the morning but improving with movement. He had a history of back surgery 20 years prior for a herniated disc. He otherwise denied a history of autoimmune disease, fever or chills, joint pains, rashes, muscle aches, or oral ulcers. He denied a history of trauma, use of blood thinners, history of bleeding disorders, or sickle cell disease. His past medical history was unremarkable, and he did not have a history of diabetes. He did not take any medications. His family history was significant for his mother having rheumatoid arthritis.